The influence of age, gender and income on Australians’ expectations of clothing lifespan - Payne, Alice; Jiang, Xinru; Street, Paige; Leenders, Mark; Nguyen, Ninh; Pervan, Simon; Swee Lin Tan, Caroline (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Extending clothing lifespans is a crucial step in advancing the transition to a circular economy. Past studies have highlighted the need to distinguish between social and technical lifespans of clothing (Laitala et al., 2018), as well as how/when to measure lifespan, whether in number of wears or number of years (Klepp et al., 2020). While research has been conducted on clothing lifespans in European contexts (WRAP 2019) and in Europe, Asia and the USA (Laitala & Klepp, 2020), this area remains underexplored in Australia, which presents a unique cultural and economic landscape. This paper investigates the expected lifespans of clothing in Australian households. Factors such as age, gender, and income can significantly impact how long consumers expect their clothing to last. By examining these variables, this research can provide insights into consumer behaviour and preferences, which can inform targeted interventions and educational campaigns to promote sustainable clothing practices.